Immunosuppression Enhances Oncolytic Adenovirus Replication and Antitumor Efficacy in the Syrian Hamster Model - Thomas, Maria A (2008)
We recently described an immunocompetent Syrian hamster model for oncolytic adenoviruses (Ads) that permits virus replication in tumor cells as well as some normal tissues. This model allows exploration of interactions between the virus, tumor, normal organs, and host immune system that could not be examined in the immunodeficient or nonpermissive animal models previously used in the oncolytic Ad field. Here we asked whether the immune response to oncolytic Ad enhances or limits antitumor efficacy. We first determined that cyclophosphamide (CP) is a potent immunosuppressive agent in the Syrian hamster and that CP alone had no effect on tumor growth. Importantly, we found that the antitumor efficacy of oncolytic Ads was significantly enhanced in immunosuppressed animals. In animals that received virus therapy plus immunosuppression, significant differences were observed in tumor histology, and in many cases little viable tumor remained. Notably, we also determined that immunosuppression allowed intratumoral virus levels to remain elevated for prolonged periods. Although favorable tumor responses can be achieved in immunocompetent animals, the rate of virus clearance from the tumor may lead to varied antitumor efficacy. Immunosuppression, therefore, allows sustained Ad replication and oncolysis, which leads to substantially improved suppression of tumor growth.